Capturing Lived Experience: Methodological Considerations for Interpretive Phenomenological Inquiry. (19th February 2020) - Frechette, Julie; Bitzas, Vasiliki; Aubry, Monique; Kilpatrick, Kelley; Lavoie-Tremblay, Mélanie
Interpretive phenomenology presents a unique methodology for inquiring into lived experience, yet few scholarly articles provide methodological guidelines for researchers, and many studies lack coherence with the methodology's philosophical foundations. This article contributes to filling these gaps in qualitative research by examining the following question: What are the key methodological and philosophical considerations of leading an interpretive phenomenological study? An exploration of interpretive phenomenology's foundations, including Heideggerian philosophy and Benner's applications in health care, will show how the philosophical tradition can guide research methodology. The interpretive phenomenological concepts of Dasein, lived experience, existentialia, authenticity are at the core of the discussion while relevant methodological concerns include research paradigm, researcher's stance, objective and research question, sampling and recruitment, data collection, and data analysis. A study of pediatric intensive care unit nurses' lived experience of a major hospital transformation project will illustrate these research considerations. This methodological article is innovative in that it explicitly describes the ties between the operational elements of an interpretive phenomenological study and the philosophical tradition. This endeavor is particularly warranted, as the essence of phenomenology is to bring to light what is taken for granted, and yet phenomenological research paradoxically makes frequent assumptions concerning the philosophical underpinnings.